Work From Home: The Influence of Work Motivation and Work Environment on Employee Work Spirit - Dendri Jonathan; Yustina Erti Pravitasmara Dewi (Universitas Pendidikan Ganesha, 2023)
During the pandemic, employees are forced to work from home (WFH) for health reasons which can lead to reduced enthusiasm in completing work. Motivation and a good or positive work environment can objectively affect employee morale with self-awareness. If good motivation is given, morale during WFH will increase. This study examines the effect of work motivation and environment on employee morale while working from home. This research is causal-comparative research. The number of samples used is 80 employee respondents. Methods of data collection using a questionnaire. The instrument used is a questionnaire sheet. This study uses multiple linear regression analysis techniques. The study found that work motivation had a positive effect on work morale. The analysis score sig 0.002 less than 0.050 that the work environment positively impacts work morale, as evidenced by a sig score of 0.010 less than 0.050. It shows that the higher the work motivation and the better the work environment, the higher the employee morale during the WFH period. Therefore, the better the work environment in an organization or company, the higher the work spirit of employees. Motivation for employees must always be given during the period of working at home.